2009
DOI: 10.1530/rep-08-0207
|View full text |Cite
|
Sign up to set email alerts
|

A deficiency of lunatic fringe is associated with cystic dilation of the rete testis

Abstract: Lunatic fringe belongs to a family of β1–3 N-acetyltransferases that modulate the affinity of the Notch receptors for their ligands through the elongation of O-fucose moieties on their extracellular domain. A role for Notch signaling in vertebrate fertility has been predicted by the intricate expression of the Notch receptors and their ligands in the oocyte and granulosa cells of the ovary and the spermatozoa and Sertoli cells of the testis. It has been demonstrated that disruption of Notch signaling by inacti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
25
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 87 publications
3
25
0
Order By: Relevance
“…Notch signaling is important for the development of the male reproductive tract, and Leydig cells particularly (Dirami et al , 2001; Tang et al , 2008; Hahn et al , 2009; Defalco et al , 2013). Perturbation of Notch signaling in granulosa cells results in MOFs, defective meiotic maturation and loss of oocytes (Hahn et al , 2005; Trombly et al , 2008; Manosalva et al , 2013; Xu and Gridley, 2013; Vanorny et al , 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Notch signaling is important for the development of the male reproductive tract, and Leydig cells particularly (Dirami et al , 2001; Tang et al , 2008; Hahn et al , 2009; Defalco et al , 2013). Perturbation of Notch signaling in granulosa cells results in MOFs, defective meiotic maturation and loss of oocytes (Hahn et al , 2005; Trombly et al , 2008; Manosalva et al , 2013; Xu and Gridley, 2013; Vanorny et al , 2014).…”
Section: Discussionmentioning
confidence: 99%
“…In rodents and humans, aberrant Notch activity was associated with male infertility [17], [19], [21], [22], [24], [25]. However, other studies [23], [26] reported that most of Notch pathway components are not transcribed in the mouse testis and that Notch blockage in germ and Sertoli cells had no effect on spermatogenesis.…”
Section: Introductionmentioning
confidence: 99%
“…While loss of Lfng may cause perinatal lethality, Lfng null homozygotes in a FVB/C57BL/6 mixed genetic background live for several months, although they are small, lack a tail, and are infertile (2022). Deletion of Mfng or Rfng separately or together has no obvious effects on development or fertility (20, 23, 24).…”
Section: Introductionmentioning
confidence: 99%